PENGGUNAAN MEDIA E–COMIC UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 4 MI AL-ADZIIM - Nurwaliyah, Wilan; Koswara Adiredja, Rajji; Widyaningsih, Yenni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading skills are part of a literacy culture that must be cultivated from an early age. However, the reality on the ground shows that many elementary school students still experience difficulties with reading comprehension. This study aims to improve the reading comprehension skills of fourth-grade elementary school students through the use of e-comics. This is motivated by the students' low ability to understand reading content in Indonesian language lessons. The method used was Classroom Action Research (CAR), implemented in two cycles, with stages of planning, implementation, observation, and reflection. The study subjects were 19 fourth-grade students. Data were collected through reading comprehension tests and student response questionnaires regarding learning using e-comics. The results showed that the use of the e-comic entitled